Construction of precision sMDT detector for the ATLAS Muon Spectrometer upgrade. (1st January 2023) - Amidei, D.; Anderson, N.; Chen, A.; Carpenter, E.; Cooperrider, L.; Dai, T.; Diehl, E.; Ferretti, C.; Guo, Y.; Li, J.; Meng, X.; Nelson, K.; et al.
Abstract: This paper describes the small-diameter monitored drift-tube detector construction at the University of Michigan as a contribution to the ATLAS Muon Spectrometer upgrade for the high-luminosity Large Hadron Collider at CERN. Measurements of the first 30 chambers built at Michigan show that the drift tube wire position accuracy meets the specification of 20 μm. The positions of the platforms for alignment and magnetic field sensors are all installed well within the required precision. The cosmic ray test measurements show single wire tracking resolution of 100 ± 7 μm with an average detection efficiency above 99%. The infrastructure, tooling, techniques, and procedures for chamber production are described in detail. The results from the chamber quality control tests of the first 30 constructed chambers are reported.